2001
DOI: 10.1051/jp4:2001835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ausaging on the morphology of martensite in an Fe-25%Ni-7.5%Si alloy

Abstract: Abstract. The martensitic transformations in an Fe-25%Ni-7.5%Si (mass%) alloy ausaged under various conditions were investigated by means of optical and transmission electron microscopy, differential scanning calorimetry, electrical resistivity-temperature measurements and hardness-testing. It was clarified that nanoscale particles of Y'-(Ni,Fe) 3 Si with Ll 2 structure were formed in the austenite matrix by ausaging between 400 and 600°C, while no precipitation occurred due to ausaging at 700°C. The Ms temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Ni-(0-63.3)at.%Fe- (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)at.%Si and Ni-(0-64)at. %Fe-(4-30)at.%Al alloys were prepared from pure Fe (99.9%), Ni (99.9%), Si (99.999%) and Al (99.7%) by induction melting in Al 2 O 3 crucibles under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ni-(0-63.3)at.%Fe- (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)at.%Si and Ni-(0-64)at. %Fe-(4-30)at.%Al alloys were prepared from pure Fe (99.9%), Ni (99.9%), Si (99.999%) and Al (99.7%) by induction melting in Al 2 O 3 crucibles under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 98%
“…This fact suggests that there are attractive interactions between Fe or Ni and Si. Recently, the present authors have shown that aging for the g austenite phase, namely, 'ausaging', induces a coherent precipitation of the metastable g 0 -L1 2 phase in the g austenite matrix [13][14][15]. The g 0 phase precipitates coherent with the matrix and strongly influences the g/a 0 (A2 or BCT) martensitic transformation in this system, bringing about a decrease of the Ms temperature, a morphological change of the martensite phase from a lenticular type to a thin plate type, the increase of tetragonality in the martensite structure, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…From this result, we can say that addition of Co to Fe-%25Ni-%5Si alloy causes the formation of lenticular martensite. It is well accepted that the martensite morphology is dependent on many factors, such as alloy composition [4,5,7], austenite grain size [19], ausaging [2,20], and martensite formation temperature [7,16], however no one has shed light on the reason why morphology exists in ferrous α martensite so far.…”
Section: Microstructure Characterization Of Martensitementioning
confidence: 99%
“…Although there are many effects that influence the formation of martensite such as austenite grain size [6,16], alloy composition [12][13]17], the austenite γ phase with L1 2 [13], martensite formation temperature [18], ausaging [19], austenite stacking fault energy [20], and the strength of martensite and austenite [21]. The reason why much morphology exists in ferrous α martensite has not been clearly understood yet.…”
Section: Morphology Of Martensite In Fe-ni-si Alloysmentioning
confidence: 99%